The scouting guide to tracking : more than 100 essential skills for identifying and trailing animals - McDougall, Len (Skyhorse Publishing, 2019)
"In Scouting's Guide to Tracking, current Scouts, Scout alumni, and readers interested in the outdoors are provided with time-tested advice on how to track big and small animals over different types of terrain. Some practical tips include: How to determine the age of tracks in any circumstance *How to recognize the distinctive marks of dozens of different species *How to track in desert, forest, snow, and grassy areas *How to identify instances when an animal has circled around or backtracked *Stalking techniques such as cold hunting, camouflaging, and using the stump method *How time and weather affect signs *And so much more! Since 1910, the Boy Scouts of America has helped build the future leaders of this country by combining educational activities and lifelong values with fun. The BSA is committed to training youth in responsible citizenship, character development, and self-reliance through participation in a wide range of outdoor activities"--